Place of CLT in Language Teaching - Ali Akbar Khansir (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2021)
This paper, in briefly reviewing the history of CLT in language teaching, provides background information about language teaching and the history of ELT in language teaching. The first portion of this paper reviews a variety of factors that have been related to language teaching, including language movement, language learning, and language acquisition, language competence and performance. The second portion focuses on CLT and its role in language teaching. In fact, CLT is the results of the changes in the British Language Teaching tradition came back to the late 1960s. The main aim of CLT for language teaching closely related to the approach of communicative competence to teach foreign or second language learners. This approach has been used by applied linguistics as a reaction way from grammar- based approaches. In addition, the grammar –based approaches include the aural –oral approach. The first area of this paper will discuss will be the central focus of this article, communicative competence approach. In 1972 Hymes as a great researcher coined the theory of Communicative competence as a scientific theory for developing the communicative competence in learners along with the grammatical competence and not merely the grammatical competence.